GENDER DISPARITY EXPERIENCED BY FEMALE CHARACTERS IN BUYA HAMKA’S NOVEL TERUSIR - Al Mardhyyah, Al Aina; Raharjo, Resdianto Permata (Philosophica: Jurnal Bahasa, Sastra, dan Budaya, 2025)
This study aims to describe the forms and causes of discrimination against women, and the struggles of female characters to fight discrimination in Hamka's novel Terusir. The following are the results of this study. First, the forms of discrimination against female characters include the individual and public domains. Discrimination in the individual domain includes marginalization of women's productivity and control over women's sexuality. Discrimination in the public domain includes limitations on women's movement and access to economic resources. Marginalization of women's productivity can be seen from the restrictions on women's movement (the marginalization of women by the power of men), Restricted women's movement is marked by prohibitions and rules of behavior determined by men, while limited economic resources include restrictions on women's work that is highly dependent on men in meeting their basic needs. Second, the factors causing discrimination include patriarchal culture, differences in social status, and customs in the form of a matrilineal system that often places women in marginalized positions. Third, the struggle undertaken by female characters in the novel to face discrimination includes protesting to obtain their rights as women, finding a new life partner who can provide welfare guarantees, and choosing to live independently to continue their lives.